Knowledge transfer in Lean management: Experience from Malaysian SME - Mohd Zahari, Fadhilah (Universitas Muhammadiyah Sidoarjo, 2019)
This study explores how SME develops knowledge transfer in Lean management, particularly the lean tacit knowledge. Lean tacit knowledge is very significant in ensuring the success of lean management implementation, yet the SMEs often found difficulties due to limited capital and resources. A single case study of Malaysian SME in automotive industry was selected for this purpose. Results show that lean training, problem solving using case study, factory visit, sharing of lean database and online learning are the common approaches that used by the studied company in developing the lean tacit knowledge. Moreover, the accomplishment of this knowledge transfer in lean management necessitate strong commitment from the employees and the top management support. This study incorporates some practical implications to the organizations that aims to implement the lean management effectively.